Comparision of Doped Optical Fiber Amplifiers - Kose, Abdullah Huzeyfe; Unverdi, N. Ozlem (IEEE, 2021)
In this study, performance analyses of doped optical fiber amplifiers which enable data transmissions over long distances by amplifying the optical signal have been conducted. The effects of frequency, optical fiber length utilized in the amplifier, type of filters employed, and the number of users on data transmission quality are analyzed by the OptiSystem 17.0 simulation software.
Keywords: Communication technologies; optical communications; optical fiber; optical fiber amplifier; bit error rate; eye diagram; Engineering; Telecommunications